(untitled) (KYAMC Journal, 2020)
Background: Coronary artery bypass graft Surgery is an established method of myocardial revascularization. Great saphenous vein is the conduit of choice for all cardiac surgeons. Objective: To compare the effect of great saphenous vein harvesting on lower limb such as swelling, pain, discharge with diabetic and non diabetic CABG patients in whom great saphenous vein was used as a conduit. Materials and Methods: It was a cross sectional study on 60 patients who underwent CABG during July 2003 to June 2005 in department of cardiovascular surgery, National Institute of Cardiovascular Diseases (NICVD). Results: The age in group A (Diabetic) ranged from 40-72 years in group B (Non Diabetic) the age range was 40-65 years. Myocardial infarction and Congestive cardiac failure were the predominant risk factors in both age groups. There was no motor or sensory disturbances post operatively. Some patients developed swelling, tenderness, paresthesia in both group but it was not statistically significant. Conclusion: Morbidity occurs in both diabetic and non diabetic patients with certain complications like numbness, paresthesia, swelling etc. at the harvesting site. KYAMC Journal Vol. 11, No.-2, July 2020, Page 59-61